2018
DOI: 10.1371/journal.pone.0199657
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory function in spinal muscular atrophy: Age-related patterns of progression

Abstract: Individuals with spinal muscular atrophy (SMA) type 3 are able to walk but they have weakness, gait impairments and fatigue. Our primary study objective was to examine longitudinal changes in the six-minute walk test (6MWT) and to evaluate whether age and SMA type 3 subtype are associated with decline in ambulatory function. Data from three prospective natural history studies were used. Seventy-three participants who performed the 6MWT more than once, at least 6 months apart, were included; follow-up ranged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 27 publications
(35 reference statements)
3
74
1
Order By: Relevance
“…A longitudinal natural history study of ambulatory patients with SMA type III showed that 6MWT trajectories were age‐dependent . The mean rate of change in 6MWT distance improved by 9.8 meters/year in patients <6 years of age, but declined by 20.8 meters/year in adolescents and young adults 11–19 years of age, regardless of age at time of diagnosis . In this study, 5 participants were >11 years old at baseline and 3 additional participants became ≥11 years old during the study.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…A longitudinal natural history study of ambulatory patients with SMA type III showed that 6MWT trajectories were age‐dependent . The mean rate of change in 6MWT distance improved by 9.8 meters/year in patients <6 years of age, but declined by 20.8 meters/year in adolescents and young adults 11–19 years of age, regardless of age at time of diagnosis . In this study, 5 participants were >11 years old at baseline and 3 additional participants became ≥11 years old during the study.…”
Section: Discussionmentioning
confidence: 53%
“…Older children and adolescents with SMA are more at risk for declining ambulatory function . A longitudinal natural history study of ambulatory patients with SMA type III showed that 6MWT trajectories were age‐dependent .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations